ANALISIS SOSIOLOGI DAN ANTROPOLOGI HUKUM EKONOMI SYARIAH PADA PUTUSAN SENGKETA MURABAHAH DI PENGADILAN AGAMA KOTA CIREBON (Perkara Nomor 1/ Pdt.G.S/2020/Pa.Cn) - Fadli Daud Abdullah; Tajul Arifin; Abdal (CV. Strata Persada Academia, 2023)
This research explores the settlement of Murabahah disputes through sociological and anthropological studies of Islamic economic law. The focal point of this analysis is Case Number 1/Pdt.G.S/2020/Pa.Cn, which is a lawsuit related to the Murabahah transaction heard at the Cirebon Religious Court. This study utilized qualitative research methods, which were collected through secondary data. The result of this study is that the decision-making process in resolving Murabahah disputes at the Cirebon Religious Court significantly reflects the socio-anthropological dimensions of Islamic economic law. This includes recognizing the social and economic impacts of sharia transactions, particularly the large material losses resulting from defaults. This underscores the importance of Sharia norms, ethical considerations in transactions, and social responsibility in ensuring fairness in the Sharia economy. In addition, it recognizes the challenges faced in reaching solutions within the framework of Sharia economics and emphasizes the importance of collaboration among the parties involved in the process. Ultimately, the implications of this judgment highlight how social and cultural elements in Sharia-compliant societies influence economic transactions and provide a comprehensive understanding of the dynamics of Sharia economic law in a practical context and its implications for case resolution in Religious Courts.